HUBUNGAN PENGETAHUAN IBU TENTANG GIZI DENGAN POLA PEMBERIAN MAKAN PADA BALITA DI UPTD PUSKESMAS DAWAN I KLUNGKUNG - Luh Made Artini; Ni Nyoman Budiani; Ni Made Dwi Mahayati (Jurnal Ilmiah Kebidanan Imelda, 2024)
Toddler nutrition is a health problem. Nutritional knowledge can influence toddler feeding patterns so that it can improve toddler nutrition. This study aims to determine the relationship between maternal knowledge about nutrition and feeding patterns for toddlers at the Regional Technical Implementation Unit of the Dawan I Klungkung Community Health Center. This type of quantitative research uses correlation analytical methods with a cross-sectional approach. The research was conducted March 3rd week to April 3rd week of 2024. Samples were taken using the proportional sampling method totaling 97 respondents. The research instrument uses a questionnaire via Google Form. The results of univariate data analysis were that the mother had a good level of knowledge (79%) and appropriate feeding patterns (90,7%) while bivariate analysis using the contingency test obtained a p value <0,05. The conclusion of this research is that there is a relationship between mothers' knowledge about toddler nutrition and toddler feeding patterns. It is hoped that the Dawan I Klungkung Regional Technical Implementation Unit will hold a routine program for posyandu activities related to nutrition education for toddlers.